What to do about bilateral credit limits in the LVTS when a closure is anticipated: Risk versus liquidity sharing among LVTS participants - Sean O'Connor; Greg Caldwell (Bank of Canada, 2008)
The authors examine the effect of a trade-off between shared credit risk and liquidity efficiency, among participants in Tranche 2 of the Large Value Transfer System (LVTS T2), on their decisions to leave open, or close, their bilateral credit limits (BCLs) to a participant at risk of imminent closure. The authors' analysis considers a network of three banks, in a settlement system similar to the LVTS T2. Although it is widely believed that closure of one bank is imminent, the exact timing of the closure during or after the settlement cycle is uncertain. The other two banks face an open or close choice regarding their BCLs to the problem participant. Based on the expected net payoff of each choice, which includes the value of network externalities, the analysis shows that, when the expected credit loss is sufficiently low, an open-BCL pure-strategy Nash equilibrium can exist and can be Pareto efficient. This result dispels the generality of the frequent assertion that participants in the LVTS T2 will close their BCLs to a participant that is subject to imminent closure.
Keywords: G21; L13; L14; 330; Financial institutions; Financial services; Payment; clearing; and settlement systems; Bankensystem; Verrechnungsverkehr; Kreditrisiko; Bankenliquidität; Pareto-Optimum; Theorie